Does a Memorable Experience Exist During the Covid-19 Pandemic? a Natural Attraction Study - Andrianto, Tomy; Septyandi, Chandra Budhi; Hukma Shabiyya, Agustin (Politeknik Negeri Bandung, 2022)
During Pandemic Covid-19 natural attractions have become one of the favorite place to visit even though there are various restrictions on movement and activities. Most of the visitors try to explore unforgettable visiting experience during their visit. The aim of this research is to understand whether the visitors able to access a memorable experience during the Covid-19 pandemic at natural tourist attractions. This research aplied quantitative methods by using descriptive analysis from online survey of 100 respondents who visited Situ Pattengang as one of natural attraction from May to July 2021. As a result, visitors still able to access several memorable experiences but lacking several others. The highest dimension turns out to be refreshment out of daily activities, then hedonism experience and uniqueness in novelty. Then followed by interaction with local communities. While the third lowest dimension is involvement with activities, meaningfulness, and knowledges.